The Effect of Company Performance on Dividend Policy in Manufacturing Companies - Onny Kusuma; Hatane Semuel (Petra International Journal of Business Studies, 2019)
Companies in managing their finances are always faced with three important issues that are interrelated. The three problems are investment decisions, funding decisions and dividend policy decisions. This study will be focusing on dividend policy decision. Not all companies distribute dividend even when they have high profit/liquidity level or because they need money to pay interest. This study investigates and aim to analyze the effect of company performance to dividend policy in manufacturing companies. Company performance used as variables are: profitability, leverage, and liquidity. The author will analyze the direct effect from profitability, leverage, and liquidity with company dividend policy. After that by using liquidity as moderating variable, the author will analyze wether high liquidity level can strengthen company decision to distribute dividends. The sample for this study are 77 manufacturing industry companies listed on the Indonesia Stock Exchange in 2010-2016 which distributed dividends. Research data is taken from annual financial report data published by the sample companies. The data in this study were processed with the help of SEM smartPLS 3.0 model. This study explains the impact of profitability, leverage, and liquidity factors on dividend policy and wether liquidity can be used to strengthen or weaken the relationship between profitability to dividend policy and leverage to dividend policy.